Epigenetic Biomarkers and the Wnt/β-Catenin Pathway in Opisthorchis viverrini-associated Cholangiocarcinoma: A Scoping Review on Therapeutic Opportunities. - Alok Kafle; Sutas Suttiprapa; Mubarak Muhammad; Jan Clyden B Tenorio; Roshan Kumar Mahato; Norhidayu Sahimin; Shih Keng Loong (PLoS Neglected Tropical Diseases)
Background Epigenetic modifications, such as DNA methylation and histone modifications, are pivotal in regulating gene expression pathways related to inflammation and cancer. While there is substantial research on epigenetic markers in cholangiocarcinoma (CCA), Opisthorchis viverrini-induced cholangiocarcinoma (Ov-CCA) is overlooked as a neglected tropical disease (NTD) with limited representation in the literature. Considering the distinct etiological agent, pathogenic mechanisms, and pathological manifestations, epigenetic research plays a pivotal role in uncovering markers and potential targets related to the cancer-promoting and morbidity-inducing liver fluke parasite prevalent in the Great Mekong Subregion (GMS). Emerging studies highlight a predominant hypermethylation phenotype in Opisthorchis viverrini (O. viverrini) tumor tissues, underscoring the significance of abnormal DNA methylation and histone modifications in genes and their promoters as reliable targets for Ov-CCA. Principal findings Relevant published literature was identified by searching major electronic databases using targeted search queries. This process retrieved a total of 81 peer-reviewed research articles deemed eligible for inclusion, as they partially or fully met the pre-defined selection criteria. These eligible articles underwent a qualitative synthesis and were included in the scoping review. Within these, 11 studies specifically explored Ov-CCA tissues to investigate potential epigenetic biomarkers and therapeutic targets. This subset of 11 articles provided a foundation for exploring the applications of epigenetics-based therapies and biomarkers for Ov-CCA. These articles delved into various epigenetic modifications, including DNA methylation and histone modifications, and examined genes with aberrant epigenetic changes linked to deregulated signalling pathways in Ov-CCA progression. Conclusions This review identified epigenetic changes and Wnt/β-catenin pathway deregulation as key drivers in Ov-CCA pathogenesis. Promoter hypermethylation of specific genes suggests potential diagnostic biomarkers and dysregulation of Wnt/β-catenin-modulating genes contributes to pathway activation in Ov-CCA progression. Reversible epigenetic changes offer opportunities for dynamic disease monitoring and targeted interventions. Therefore, this study underscores the importance of these epigenetic modifications in Ov-CCA development, suggesting novel therapeutic targets within disrupted signalling networks. However, additional validation is crucial for translating these novel insights into clinically applicable strategies, enhancing personalised Ov-CCA management approaches.